The Effects of Competency-Based Training, Shift Scheduling, and Resource Availability on Employee Job Performance: the Mediating Role of Work Engagement - Amal Prihatono (Newinera Publisher, 2026)
This study aims to analyze the effects of competency-based training, shift scheduling, and resource availability on employee job performance at the Traditional Health Center Sehat Harmoni Indonesia, with work engagement serving as a mediating variable. This study employed a quantitative research design with a cross-sectional approach. The population consisted of all employees of the Traditional Health Center Sehat Harmoni Indonesia. The sampling technique used was saturated sampling (census sampling), in which all members of the population were included as respondents. The total sample in this study was 50 employees. Data were collected through a structured questionnaire. The SEM-PLS analysis technique using SmartPLS 3 was applied to evaluate the direct and indirect effects within the proposed model. The findings reveal that competency-based training, shift scheduling, and resource availability significantly improve both work engagement and employee job performance, with resource availability showing the strongest direct effect. Work engagement also positively influences performance and serves as an effective mediator, indicating that these organizational practices enhance job outcomes both directly and indirectly by increasing employee engagement. Overall, well-designed training, effective scheduling, and adequate resources are essential for strengthening employee performance at Sehat Harmoni Indonesia. Future studies are recommended to include additional variables such as work motivation, leadership style, organizational culture, or job satisfaction to gain a broader understanding of factors influencing employee performance. Researchers may also employ longitudinal designs or expand samples across multiple traditional health centers to improve generalizability. Additionally, qualitative or mixed-method approaches could provide deeper insights into how training, shift scheduling, and resource availability shape employee experiences and performance.